High precision technique of measuring the reflectance of reflective materials - Lim, Boon Han (2001)
A new method of reflectivity measurement is proposed and tested in this Ph.D. study. The method employs fast rotating reference mirror and certain geometry configuration to alternately deliver the light via a sample mirror or by passing it to a photo detector. It has proved to reach a precision of 2 x lo4 reflectance unit. The precision is at least ten times better than that of conventional reflectometer used in solar energy applications. With good repeatability, the durability test of mirrors is camed out for only one month enabling significant specular reflectance losses of mirrors to be observed instead of more than a year in the conventional case. The reflectometer has provided solutions to few problems that limit the conventional reflectometer. Firstly, the time interval between the collection of reference signal and sample signal is short, therefore, this can reduce the effect due to the changes of environment conditions, particularly, the intensity fluctuation of light source and others. Secondly, by taking advantage of the short measurement time, a large number of readings can be made to suppress the noise level. Thirdly, the value of the reflectance of the reference mirror is not required. In the system, an accurate positioning of laser beam on the photo detector is achieved by a position sensor using a pair of dual cells that acts as an optical lever as well as a position transducer for the feedback system.